Funny farm [videorecording (DVD)] - Hill, George Roy, 1921-2002; Chase, Chevy; Smith-Osborne, Madolyn, 1957-; Maher, Joseph, 1933-1998; Gilpin, Jack, 1951- (Warner Home Video, 1999)
A Manhattan sportswriter abandons his career for life in the country.